The real-time measurement of football aerodynamic loads under spinning conditions. (December 2017) - Passmore, Martin A; Tuplin, Simon; Stawski, Aleksander
Aerodynamic effects play an important part in any sport where the ball experiences significant periods of free flight. This article investigates the aerodynamic forces generated when a football is spinning quickly to generate swerve and more slowly to generate more erratic flight. The work reports on the application of an experimental method that measures the aerodynamic loads on a non-spinning, slowly spinning and fast spinning football, using a phase-locked technique so that orientation-dependent and steady 'Magnus' forces can both be determined. The results demonstrate that the orientation-dependent aerodynamic loads, widely seen in non-spinning data in the literature, surprisingly persist up to the highest spin rates reported. When predicting ball flight, it is generally assumed that at low spin rates a quasi-static assumption is acceptable, whereby forces measured on a non-spinning ball, as a function of ball orientation, apply for the spinning case. Above an arbitrary spin rate, the quasi-static assumption is replaced with the assumption of a steady 'Magnus' force that is a function of spin rate and ball speed. Using a flight model, the quasi-static assumption is shown to be only applicable for the lowest spin rates tested and the assumption of a steady 'Magnus' force is only applicable at the highest spin rates. In the intermediate spin rates (20–40 r/min), the persistence of the orientation effects is shown to have sufficient effect on the flight to be an important additional consideration.